Changes in Cough Reflex Sensitivity in Children After Removal of Hypertrophied Adenoid Tissue - Sojak J (Journal of Asthma and Allergy, 2022)
Jan Sojak,1 Peter Durdik,2 Eva Omar Mohamedova,3 Marian Grendar,4 Miroslava Lucanska,5 Martin Jozef Pec,6 Milos Tatar,7 Renata Pecova7 1Clinic of Otorhinolaryngology and Head and Neck Surgery, Faculty of Medicine, Slovak Medical University in Bratislava, Central Military Hospital in Ruzomberok, Ruzomberok, Slovak Republic; 2Clinic of Children and Adolescent, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, University Hospital Martin, Martin, Slovak Republic; 3Outpatient Department of Clinical Immunology and Allergology in Ruzomberok, Ruzomberok, Slovak Republic; 4Biomedical Center, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, Martin, Slovak Republic; 5Clinic of Otorhinolaryngology and Head and Neck Surgery, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, University Hospital Martin, Martin, Slovak Republic; 6Clinic of Internal Medicine I, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, University Hospital Martin, Martin, Slovak Republic; 7Department of Pathological Physiology, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, Martin, Slovak RepublicCorrespondence: Renata Pecova, Department of Pathological Physiology, Jessenius Faculty of Medicine in Martin, Comenius University in Bratislava, Malá Hora 4C, Martin, 036 01, Slovak Republic, Tel +421 43 2633 622, Email renata.pecova@uniba.skPurpose: The co-occurrence of adenoids and chronic cough is common in children. The goal of this research was to specify changes in cough reflex sensitivity as a result of adenoid tissue removal.Patients and Methods: The sample group consisted of 17 children (six boys and 11 girls, aged 4– 12 years, mean age 6.24 years), all of them possessing symptoms of chronic cough and adenoids, confirmed by nasal fiberoptic endoscopy. This sample group underwent cough reflex sensitivity assessment, which took place both prior to and after endoscopic adenoidectomy. The definition of the cough reflex sensitivity is the lowest capsaicin concentration that caused two (C2) or five (C5) coughs. Capsaicin aerosol in ascending concentrations (from 0.61 to 1250 μmol/L) was inhaled by a single-breath method (KoKo DigiDoser), with the addition of an inspiratory flow regulator valve (RIFR).Results: Concentrations of capsaicin causing two (C2) and five coughs (C5) were reported. Cough sensitivity (geometric mean with 95% CI) for C2 was 31.86 (12.98– 78.18) μmol/L preoperatively and 11.97 (6.16– 23.26) μmol/L postoperatively (P=0.064). Cough sensitivity for C5 was 234.91 (97.19– 567.77) μmol/L preoperatively and 69.13 (29.08– 164.35) μmol/L postoperatively (P=0.022). The children’s pulmonary function was within the normal range.Conclusion: In our study, adenoidectomy significantly increased cough reflex sensitivity in non-atopic children suffering from chronic cough.Keywords: adenoids, adenoidectomy, cough, cough reflex sensitivity, chronic cough, children